2008
DOI: 10.4049/jimmunol.180.10.6439
|View full text |Cite
|
Sign up to set email alerts
|

The Physiology of Leukocyte Recruitment: An In Vivo Perspective

Abstract: The mechanisms of leukocyte recruitment have been studied extensively in vitro and have shed light on the basic molecular structure-function relationship of adhesion and signaling molecules involved in this essential immune response. This review will summarize how these in vitro observations extend to leukocyte behavior in inflamed blood vessels in the microcirculation. We highlight physiological results that might not have been predicted from in vitro systems. Special attention is placed on the physiology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
208
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(219 citation statements)
references
References 96 publications
(97 reference statements)
5
208
0
6
Order By: Relevance
“…Activation of endothelial cells during inflammatory responses is typically induced by proinflammatory cytokines, such as TNF-α and IL-1β (25), resulting in leukocyte recruitment at the sites of cellular damage. The process of leukocyte recruitment occurs through the expression of several adhesion molecules and chemokines such as MIF, which promotes the expression of endothelial P-selectin and arrest of leukocyte rolling (26); sICAM-1, which results in leukocyte adhesion (25); and MCP-1 and IL-8, which promote leukocyte emigration from the vasculature (27).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of endothelial cells during inflammatory responses is typically induced by proinflammatory cytokines, such as TNF-α and IL-1β (25), resulting in leukocyte recruitment at the sites of cellular damage. The process of leukocyte recruitment occurs through the expression of several adhesion molecules and chemokines such as MIF, which promotes the expression of endothelial P-selectin and arrest of leukocyte rolling (26); sICAM-1, which results in leukocyte adhesion (25); and MCP-1 and IL-8, which promote leukocyte emigration from the vasculature (27).…”
Section: Discussionmentioning
confidence: 99%
“…P recise targeting of leukocytes to their marked battlegrounds is a key strategy for victory by the immune defense (1). Although this complex process has been a subject of intensive research for decades (2), many of the involved signaling pathways are still poorly understood (3).…”
Section: Integrin Regulation During Leukocyte Recruitmentmentioning
confidence: 99%
“…Although this complex process has been a subject of intensive research for decades (2), many of the involved signaling pathways are still poorly understood (3). Different sequential recruitment steps have been identified that each necessitates distinct functioning of particular members of the integrin family of adhesion molecules (1). These plasma membrane proteins feature a dual role of sensing and interacting with the surrounding environment (4).…”
Section: Integrin Regulation During Leukocyte Recruitmentmentioning
confidence: 99%
“…This process requires that circulating leukocytes undergo a well-defined series of adhesion molecule-mediated interactions within the microvasculature at the site of inflammation (1,2). This sequence is typically initiated by selectin-mediated leukocyte rolling on the endothelial surface, followed by integrin-mediated arrest in response to chemoattractant-derived signals, and subsequent transmigration into tissues.…”
mentioning
confidence: 99%